The Application of Laozi's Leadership Spirit in Contemporary Higher Education - Wenyao, Pang; Mutong, Marivic B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This paper examines the application of Laozi's leadership spirit in contemporary higher education, focusing on the practice of integrating Laozi's ideas into teaching and policies, as well as the enlightenment of Laozi's educational philosophy for teachers and students. Employing a qualitative design, an interview with two deans, 10 teacher representatives, and 6 class monitors from the School of Electrical Engineering at Shaanxi Polytechnic Institute of Industry was conducted. The study found that the school effectively integrates Laozi's "governing by doing nothing" via flexible curricula, process-oriented teaching, and relaxed policies. This balances academic freedom with institutional constraints while fostering student autonomy and sustainable development. The areas of Laozi's philosophy inspire self-management through non-intervention, soft communication to resolve conflicts, process-focused learning, and moral modelling, promoting educational harmony.